2022
DOI: 10.1136/bmjgh-2021-008069
|View full text |Cite
|
Sign up to set email alerts
|

Health service utilisation during the COVID-19 pandemic in sub-Saharan Africa in 2020: a multicountry empirical assessment with a focus on maternal, newborn and child health services

Abstract: IntroductionThere are concerns about the impact of the COVID-19 pandemic on the continuation of essential health services in sub-Saharan Africa. Through the Countdown to 2030 for Women’s, Children’s and Adolescents’ Health country collaborations, analysts from country and global public health institutions and ministries of health assessed the trends in selected services for maternal, newborn and child health, general service utilisation.MethodsMonthly routine health facility data by district for the period 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 26 publications
3
59
2
Order By: Relevance
“… 67 , 68 Some challenges in scaling the testing and diagnostic facilities for COVID-19 in SSA include gaps in service delivery and health systems, unskilled staffing, poor healthcare financing, sociocultural values, and the absence of infrastructure and technology to initiate and maintain diagnostic services. 69 71 This finding indicates the need for reform programs for strengthening and sustaining healthcare systems through appropriate health policy, adequate governmental focus and investment, and capacity-building in human resources, governance, and financing.…”
Section: Discussionmentioning
confidence: 99%
“… 67 , 68 Some challenges in scaling the testing and diagnostic facilities for COVID-19 in SSA include gaps in service delivery and health systems, unskilled staffing, poor healthcare financing, sociocultural values, and the absence of infrastructure and technology to initiate and maintain diagnostic services. 69 71 This finding indicates the need for reform programs for strengthening and sustaining healthcare systems through appropriate health policy, adequate governmental focus and investment, and capacity-building in human resources, governance, and financing.…”
Section: Discussionmentioning
confidence: 99%
“…At the start of the COVID-19 pandemic, statistical models projected maternal and child mortality increases based on hypothesized service disruption scenarios [10][11][12]. Multiple sources have since confirmed increases in adverse maternal outcomes but lower than expected utilization of reproductive, maternal, and child (RMNCH) services during the pandemic [13][14][15][16]. Studies have quantified decreases in total health facility attendance, complementing the qualitative reports by health workers and stakeholders [13,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Our ndings complement the report of previous quantitative studies in Nigeria: Adelekan et al reported a 2-6% reduction in utilisation of various SRH services in primary healthcare settings in Nigeria [16] while Balogun and colleagues reported that about a third of the women seeking SRH care in Lagos during the lockdown had a challenge with accessing orthodox services [18]. Results from other settings also show that the Nigerian experience is similar to what obtains in several sub-Saharan African countries and other lowand middle-income settings [12,23,[27][28][29].…”
Section: Discussionmentioning
confidence: 91%